The Use of Market Data and Accounting Data in Hedging Against Consumer Price Inflation - Bernard, Victor L. (Journal of Accounting Research, 1984)
This paper examines the use of alternative information sets in the construction of inflation hedge portfolios. The study is motivated by consideration of the investor's problem in a multiperiod world. Several authors (e.g., Merton [1973] and Breeden [1979]) have shown that in a multiperiod setting, optimal investment behavior will, in general, involve holding portfolios that can be used to hedge against changes in certain relevant states of nature. One potentially relevant state of nature is the rate of inflation in general prices (Jones [1982] and Elton, Gruber, and Rentzler [1983]). In contrast to prior related research, the empirical results indicate that it is possible to construct inflation hedge portfolios successfully, if certain accounting information is used. However, portfolios constructed on the basis of historical security price information do not serve as effective hedges. One contribution of this paper is to demonstrate the potential usefulness of accounting information to a price-taking investor. Although financial statements play an important role in the setting of equilibrium